Specialties of coal seams mining under conditions of Western Donbas - Demydov, M.S.; Astafiev, D.O.; Kaminski, P. (Розробка родовищ, 2015)
Problems that limited usage of plow systems in conditions of Western Donbas are considered. Analysis of plow systems work in Ukraine and abroad is given. Prospects for further research and sharp problems solution in coal industry of Ukraine are established. Розглянуто проблеми, які обмежують застосування стругової техніки в умовах Західного Донбасу. Наведено аналіз роботи стругів в Україні та за кордоном. Встановлено перспективи подальших досліджень та вирішення гострих проблем вугільної галузі України. Рассмотрены проблемы, ограничивающие применение струговой техники в условиях Западного Донбасса. Приведен анализ работы стругов в Украине и за рубежом. Установлены перспективы дальнейших исследований и решений острых проблем угольной отрасли Украины.